1998
DOI: 10.1021/jf980392h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preheating on Properties of Aggregates and of Cold-Set Gels of Whey Protein Isolate

Abstract: Various concentrations (1-9%) of whey protein (WP) isolate solutions were heat-denatured at 80°C for 30 min. Size exclusion HPLC and dynamic light scattering revealed formation of soluble aggregates in 3-9% denatured WP solution. Size and content of the aggregates increased with increases in preheated WP concentration. The 4-9% denatured WP solutions were diluted to 3% WP with distilled water. Upon addition of CaCl 2 (20 mM) or glucono-δ-lactone (0.6%, w/v), all 3% denatured WP solutions formed gels at 37°C. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 13 publications
4
56
0
3
Order By: Relevance
“…The presence of 5 mM CaCl 2 induced extensive polymerisation that was not seen in non-dissociating PAGE. This is in agreement with Ju and Kilara (1998a), who reported that such a calcium chloride concentration is sufficient to bring about aggregation. Increasing the concentration of calcium chloride up to 15 mM caused almost all monomers to become involved in polymer formation (Fig.…”
Section: Article In Presssupporting
confidence: 93%
“…The presence of 5 mM CaCl 2 induced extensive polymerisation that was not seen in non-dissociating PAGE. This is in agreement with Ju and Kilara (1998a), who reported that such a calcium chloride concentration is sufficient to bring about aggregation. Increasing the concentration of calcium chloride up to 15 mM caused almost all monomers to become involved in polymer formation (Fig.…”
Section: Article In Presssupporting
confidence: 93%
“…Interactions of inulin with some carbohydrates such as waxy maize starch (Zimeri and Kokini, 2003), maltodextrins (van Duynhoven et al, 1999) or pectin (Giannouli et al, 2003) have also been analysed. The rheological behaviour of salt-induced whey protein gels is very well documented (Barbut, 1995;Barbut and Foegeding, 1993;Glibowski et al, 2006a,b;Ju and Kilara, 1998), but most reports on whey protein interactions with carbohydrates refer to heat-set gels (Gustaw et al, 2003;Lupano and Gonzalez, 1999;Tavares and Lopes da Silva, 2003). Recently, the interaction of whey proteins with polysaccharides in acid-induced cold set gels has been described in various publications (van den Berg et al, 2007(van den Berg et al, , 2008de Jong and van de Velde, 2007) but there are few reports on the analysis of interactions in salt-induced cold set gels (Bryant and McClements, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…In case of the latter, mainly NaCl and CaCl 2 were studied with regard to cold-set gelation [14][15][16][17][18]. These cold-set gels generally showed higher gel strength and water holding capacity than gels formed by heat-induced gelation [17][18][19]. To a much lesser extent the mechanism of cold gelation as induced by minerals such as Fe 2+ [12,20,21] and Mg 2+ [22] has been studied.…”
Section: Introductionmentioning
confidence: 99%